2019
DOI: 10.1111/oik.06149
|View full text |Cite
|
Sign up to set email alerts
|

Detrital traits affect substitutability of a range‐expanding foundation species across latitude

Abstract: Climate‐driven range shifts of foundation species could alter ecosystem processes and community composition by providing different resources than resident foundation species. Along the US Atlantic coast, the northward expanding foundation species, black mangrove Avicennia germinans, is replacing the dominant salt marsh foundation species, marsh cordgrass Spartina alterniflora. These species have distinct detrital attributes that ostensibly provide different resources to epifauna. We experimentally examined how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 91 publications
(141 reference statements)
0
15
2
Order By: Relevance
“…These conditions likely favored higher breakdown rates of labile organic matter (S. alterniflora and green tea litter), but we did not observe this pattern for recalcitrant litter (A. germinans). In contrast, higher breakdown rates of A. germinans in mangrove-dominated plots suggest a possible "home field" advantage of metazoan and microbial communities adapted to and preferentially consuming recalcitrant organic matter, which has been observed in other wetland and aquatic ecosystems (Kominoski et al, 2012;Smith et al, 2019;Yeung et al, 2019). Smith et al (2019) found A. germinans litter k was two to four times higher than that of S. alterniflora litter irrespective of cell vegetation type (marsh, mangrove, and mixed-species), and it was suggested that this was because A. germinans has a lower molar C:N ratio than S. alterniflora.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These conditions likely favored higher breakdown rates of labile organic matter (S. alterniflora and green tea litter), but we did not observe this pattern for recalcitrant litter (A. germinans). In contrast, higher breakdown rates of A. germinans in mangrove-dominated plots suggest a possible "home field" advantage of metazoan and microbial communities adapted to and preferentially consuming recalcitrant organic matter, which has been observed in other wetland and aquatic ecosystems (Kominoski et al, 2012;Smith et al, 2019;Yeung et al, 2019). Smith et al (2019) found A. germinans litter k was two to four times higher than that of S. alterniflora litter irrespective of cell vegetation type (marsh, mangrove, and mixed-species), and it was suggested that this was because A. germinans has a lower molar C:N ratio than S. alterniflora.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, higher breakdown rates of A. germinans in mangrove-dominated plots suggest a possible "home field" advantage of metazoan and microbial communities adapted to and preferentially consuming recalcitrant organic matter, which has been observed in other wetland and aquatic ecosystems (Kominoski et al, 2012;Smith et al, 2019;Yeung et al, 2019). Smith et al (2019) found A. germinans litter k was two to four times higher than that of S. alterniflora litter irrespective of cell vegetation type (marsh, mangrove, and mixed-species), and it was suggested that this was because A. germinans has a lower molar C:N ratio than S. alterniflora. However, C:N of A. germinans litter from our sites was higher (66-72) (Charles et al, 2020) than that has been reported elsewhere (47-55) (Lawton-Thomas, 1997;Twilley et al, 1986), making it more similar in nutrient content to Spartina detritus (65-92) (Breteler et al, 1981;White & Howes, 1994), and making this an unlikely mechanism in our study.…”
Section: Discussionmentioning
confidence: 96%
“…We documented a correlation between mangrove host-tree genetics and fungal community differences, but does this relationship generate variation in stress tolerance among mangrove hosts? If so, this insight could broaden the current discussion of how a shift from salt marsh to mangrove dominance may shape these coastal communities (e.g., Kelleway et al, 2017;Johnston and Gruner, 2018;Smith et al, 2019;Armitage et al, 2020) by including mangrove intraspecific variation as a factor that could influence population resilience at these high-stress range limits.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, macrofaunal communities differed in marsh versus mangrove-dominated vegetation along the Atlantic coast of Florida, due to the influence of fine-scale plant structural differences and stand-level habitat attributes (Johnston & Gruner, 2018). Along the Atlantic coast, studies have noted differences in detrital-based epifaunal communities (Smith et al, 2019) Beyond just the direct effects on animals, mangrove expansion can also affect microbial (Barreto et al, 2018) and rhizosphere communities (Chen et al, 2020), which can affect abiotic conditions, biotic interactions, and biogeochemical cycling. The effects of mangrove expansion on coastal food webs and fisheries may also increase with time due to the influence of the forest developmental stage (Barimo & Serafy, 2003;Scheffel et al, 2018).…”
Section: Coa S Ta L Food Webs a Nd Fi S Herie Smentioning
confidence: 99%